Behavioral factors associated with the development of skin cancer in patients of arsenicosis (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The study was conducted to evaluate the behavioral factors associated with the development of skin cancer in arsenicosis patients. Arsenicosis patients without skin cancer were taken as control. In the sun-exposed area of the body, 57.2% of skin carcinoma was Bowen’s disease. In the covered area of the body, 56.0% was Bowen’s disease, 36% was squamous cell carcinoma and 8% was basal cell carcinoma. Again, 53.1% of case and 59.4% of control never used fertilizer and pesticide. The majorities were non-smoker (case 53.1%, control 59.3%). Mean cumulative sun exposure was more in the case group (5853.9 ± 2219.7 hours) than in the control group (2219 ± 392.4 hours) and the rate of sun exposure was also higher in the case group. In conclusion, sun exposure was significantly higher in carcinoma patients and since most of the lesions were in the covered areas of the body, it can be said that these carcinomas were due to arsenicosis and not due to sun exposure and smoking status, use of fertilizer and pesticides were not associated with the development of skin carcinoma.